O ENSINO DE HISTÓRIA EM ESCOLAS NO MEIO RURAL BRASILEIRO - Astrogildo Fernandes Silva Júnior; Selva Guimarães Fonseca (EccoS – Revista Científica)
In this text are shown the results from the Master thesis "Knowledge and practices of the History teaching in rural schools (a study performed in the City of Araguari, MG, Brazil), developed during Master in Education in the Pos-graduate program in Education from Universidade Federal de Uberlândia (PPGE/UFU), articulated to the research project "Teacher formation, knowledge and practice of History teaching" supported by the Conselho Nacional de Desenvolvimento Científico e Tecnológico -CNPq. Here the objectives were to characterize history teaching in rural schools education in the last decades and to analyze the knowledge and curricular practices from the History teaching in rural schools. We concluded that the History teaching and education in the Brazilian rural area underwent transformation in the last decades, and the knowledge and practices are built during the education experience in schools that are multicultural spaces, where distinct subjects play.